2008
DOI: 10.1007/s00244-008-9200-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sequential Isoproturon Pulse Exposure on Scenedesmus vacuolatus

Abstract: Aquatic organisms are typically exposed to fluctuating concentrations of herbicides in streams. To assess the effects on algae of repeated peak exposure to the herbicide isoproturon, we subjected the alga Scenedesmus vacuolatus to two sequential pulse exposure scenarios. Effects on growth and on the inhibition of the effective quantum yield of photosystem II (PSII) were measured. In the first scenario, algae were exposed to short, 5-h pulses at high isoproturon concentrations (400 and 1000 lg/l), each followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 23 publications
5
25
0
Order By: Relevance
“…The algae growth inhibition test was performed according to the OECD guideline 201 [26] with the green algae Pseudokirchneriella subcapitata (Chlorophyceae ; strain SAG 61.81, from the Culture Collection of Algae, Göttingen, Germany), maintained as described by Valloton et al [27]. Briefly, exponentially growing algae (initially around 50,000 cells ml −1 in sterile mineral AAP growth medium, pH 7.5) were exposed to the diluted samples over a period of 72 h, in an incubation shaker (Infors HT, Bottmingen, Switzerland) at 25 • C and 90 rpm, with continuous illumination (70 mol m −2 s −1 ) by cool-white fluorescent lamps.…”
Section: Ecotoxicity Testmentioning
confidence: 99%
“…The algae growth inhibition test was performed according to the OECD guideline 201 [26] with the green algae Pseudokirchneriella subcapitata (Chlorophyceae ; strain SAG 61.81, from the Culture Collection of Algae, Göttingen, Germany), maintained as described by Valloton et al [27]. Briefly, exponentially growing algae (initially around 50,000 cells ml −1 in sterile mineral AAP growth medium, pH 7.5) were exposed to the diluted samples over a period of 72 h, in an incubation shaker (Infors HT, Bottmingen, Switzerland) at 25 • C and 90 rpm, with continuous illumination (70 mol m −2 s −1 ) by cool-white fluorescent lamps.…”
Section: Ecotoxicity Testmentioning
confidence: 99%
“…Although this compound has been banned in several countries or restricted to 1.2 kg ha -1 year -1 since 2003 in several countries including France, it is still extensively used worldwide. Several studies have indicated the harmful effects of IPU and its metabolites on aquatic invertebrates, freshwater algae and microbial communities (Mansour et al 1999;Widenfalk et al 2008;Vallotton et al 2009). IPU and its metabolites have also been suspected to be carcinogenic to human beings and animals (Behera and Bhunya 1990;Hoshiya et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Eisenia fetida and Perionyx sansibaricus (Gobi and Gunasekaran 2010). The ecotoxicological studies suggest that butachlor may be harmful to aquatic invertebrates (Vallotton et al 2009), microbial communities (Widenfalk et al 2008) and also a possible carcinogen in animals and humans (Geng et al 2005a). It is reported as a neurotoxin (Rajyalakshmi et al 1996), genotoxin (Ateeq et al 2005;Geng et al 2005a) and carcinogen (Dwivedi et al 2012).…”
Section: Introductionmentioning
confidence: 99%